Pemberdayaan Masyarakat Berbasis Ecovillage - Sumyati, Ani; Sumpena, Deden (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
This paper aims to determine community empowerment in Cimanggung village according to Ecovillage Lestari program managers, community empowerment in Ecovillage Lestari group in Cimanggung village and community empowerment carried out by Ecovillage Lestari in Cimanggung village in ecovillage-based community empowerment at Cimanggung Village Cimanggung District District Ecovillage Sumedang. The method in this study uses descriptive study method. The results of the research conducted show that the existence of the Ecovillage Sustainable program can increase community participation in mutual cooperation. With the Ecovillage Lestari program, people are self-reliant and care about the environmental preservation that is around the Cimanggung village community.